Dampak Gaya Hidup dan Literasi Keuangan Terhadap Kecenderungan Konsumtif Mahasiswa - Masiun, Stefanus; Gustin, Markdo Anbest; Tasia, Santa Gema (Forum Kerjasama Pendidikan Tinggi, 2025)
Consumptive behavior among students is common, caused by environmental pressures to maintain a certain lifestyle and a lack of financial literacy. The purpose of this study is to determine whether lifestyle and financial literacy have a positive and significant effect on the consumptive behavior of students at the Keling Kumang Institute of Technology. This study used a sample of 84 students calculated using the Slovin formula, consisting of 3 study programs from semesters 1 to 6 with a random sampling technique because each member of the population had an equal chance of being selected, so that the sample results were more representative and unbiased. The analysis tool used was SPSS 27 V, performing all statistical tests up to the conclusion stage. The results of the study prove that lifestyle and financial literacy have a positive and significant effect on student shopping behavior, as can be seen from the F test, where Fcount is 13.276, which is greater than the Ftable value of 3.109 with a significance level of 0.000. However, partially, financial literacy has a negative effect on students' consumptive behavior, indicating that when knowledge of financial management is limited, a person will tend to behave consumptively.